Pengaruh Penerapan Model Pembelajaran Cooperative Script Dalam Meningkatkan Hasil Belajar Pada Mata Pelajaran Sejarah di SMA Negeri 3 Pematang Siantar - Ahmad Fakhri Hutauruk (Keguruan, 2022)
In class X students at SMA Negeri 3 Pematang Siantar, this study attempts to ascertain if the Cooperative Script learning methodology can achieve student learning outcomes in history topics. The Nonequivalent Control Group Design is the type of research design utilized in this study, which employs a quasi-experimental methodology. Tests, observation, and documentation were employed in data gathering procedures, while dependent and independent sample t-tests were utilized in data analysis approaches. 22 students from Class X Science served as the experimental class in this study, and 22 students from Class X Social Studies served as the control class. Based on the study's findings, it was discovered that the learning outcomes of the experimental class's students, who used the Cooperative Script learning model, were better than those of the control class's students, who used the traditional learning model. Thus, it can be said that class X students at SMA Negeri 3 Pematang Siantar may learn history substantially better using the Cooperative Script learning paradigm. This can be taken into account so that the school can use this learning model to enhance student learning outcomes. The approach the school can adopt is to organize routine teacher training sessions on innovative learning.